Carbon fiber composite material and preparation method thereof

By growing carbon nanotube arrays on the surface of carbon fibers and combining them with matrix resins and functional fillers of specific components, the problem of poor interfacial bonding performance of traditional carbon fiber composites has been solved, thereby improving the mechanical properties and electrical conductivity of the materials, making them suitable for high-performance fields such as aerospace and automotive.

CN121427271APending Publication Date: 2026-01-30中复神鹰碳纤维连云港有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511575734.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2026-01-30

AI Technical Summary

Technical Problem

Traditional carbon fiber composites suffer from poor interfacial bonding performance, resulting in weak physical anchoring and chemical bonding between the composite and the resin matrix, which affects the overall performance, long-term durability and dimensional stability of the material.

Method used

By growing carbon nanotube arrays on the surface of carbon fibers and combining them with matrix resins and functional fillers of specific components, modified carbon fiber bundles are formed, which enhance the physical bonding force and conductive network between the modified carbon fibers and the matrix resin.

Benefits of technology

It significantly improves the mechanical properties and overall electrical conductivity of carbon fiber composites, while also enhancing the material's flexibility and durability, making it suitable for applications with high weight and performance requirements, such as aerospace and automotive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121427271A_ABST
    Figure CN121427271A_ABST
Patent Text Reader

Abstract

The invention provides a carbon fiber composite material and a preparation method thereof. The composite material comprises modified carbon fiber bundles and matrix resin, the matrix resin coats the carbon fiber bundles and fills gaps in the carbon fiber bundles; the modified carbon fiber bundle comprises modified carbon fibers, and the mass ratio of the modified carbon fibers to the matrix resin is 1.2-2.4; a carbon nanotube array grows on the surface of the modified carbon fiber, the height of the carbon nanotube array is 8-20 microns, and the density of the carbon nanotube array is 60-120 / micron < 2 >. In the carbon fiber composite material, the carbon nanotube array grows on the surface of the modified carbon fiber, so that the physical binding force of the modified carbon fiber bundle and the matrix resin can be enhanced, and the mechanical property of the carbon fiber composite material is greatly improved. In addition, the carbon nanotube array grows on the surface of the modified carbon fiber, a high-conductivity network can be formed near the modified carbon fiber, and improvement of the overall conductivity of the carbon fiber composite material is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present disclosure relates to the technical field of composite materials, in particular to a carbon fiber composite material and a preparation method thereof. BACKGROUND

[0002] Carbon fiber composite materials are widely used in the fields of aerospace, rail transportation, new energy and other high-end equipment manufacturing due to their high specific strength, high specific modulus and excellent fatigue resistance.

[0003] However, the traditional carbon fiber composite material generally has the bottleneck problem of poor interfacial bonding performance. The surface of carbon fiber is chemically inert and smooth, which leads to weak physical anchoring effect and chemical bonding between the carbon fiber and the resin matrix. This weak interfacial bonding seriously restricts the overall performance of the material and affects the long-term durability and dimensional stability of the composite material. SUMMARY

[0004] To solve the problems in the related art, the present disclosure provides a carbon fiber composite material and a preparation method thereof.

[0005] According to a first aspect of some embodiments of the present disclosure, a carbon fiber composite material is provided, the composite material comprising a modified carbon fiber bundle and a matrix resin; the matrix resin coats the carbon fiber bundle and fills the gaps in the carbon fiber bundle; the modified carbon fiber bundle comprises modified carbon fibers, and the mass ratio of the modified carbon fibers to the matrix resin is 1.2-2.4. The surface of the modified carbon fiber grows an array of carbon nanotubes, the height of the array of carbon nanotubes is 8-20 μm, and the density is 60-120 per μm. 2 .

[0006] In some embodiments of the present disclosure, the matrix resin comprises the following components, and the content of each component is represented as follows in terms of mass fraction: polyethylene glycol amine grafted bisphenol A type epoxy resin 12.4-29.6 parts, polyisocyanate crosslinked polycarbonate 17.3-36.2 parts, gamma-trifluoropropyl methyl polysiloxane 3.1-18.5 parts.

[0007] In some embodiments of the present disclosure, the composite material further comprises a functional filler, and the functional filler comprises the following components, and the content of each component is represented as follows in terms of mass fraction: ferroferric oxide modified oxidized graphene 2.4-19.6 parts, dynamic crosslinking agent containing pinacol groups 0.5-8.9 parts; The iron oxide-modified graphene is arranged in the matrix resin according to a preset rule, and ionic bonds are formed between the iron oxide-modified graphene and the modified carbon fiber. The dynamic crosslinking agent containing pinacol groups connects the polyethylene glycol amine-grafted bisphenol A type epoxy resin and the polyisocyanate-crosslinked polycarbonate to form a three-dimensional network structure.

[0008] In some embodiments of this disclosure, the mass ratio of the matrix resin to the iron oxide-modified graphene is (3.6~12.1):1.

[0009] In some embodiments of this disclosure, the mass ratio of the sum of the polyethylene glycolamine-grafted bisphenol A type epoxy resin and the polyisocyanate-crosslinked polycarbonate to the dynamic crosslinking agent containing pinacol groups is (15.3~40.6):1.

[0010] According to a second aspect of the present disclosure, a method for preparing a carbon fiber composite material is provided, the method being used to prepare the carbon fiber composite material as described above; the method includes: After plasma activation treatment of the carbon fibers in the carbon fiber bundle, carbon nanotube arrays are catalytically grown on the surface of the plasma-activated carbon fibers to obtain modified carbon fibers. The modified carbon fibers and matrix resin are melt-impregnated and extruded to obtain the carbon fiber composite material; wherein the matrix resin coats the carbon fiber bundles and fills the gaps within the carbon fiber bundles.

[0011] In some embodiments of this disclosure, carbon fibers in a carbon fiber bundle are subjected to plasma activation treatment, and then carbon nanotube arrays are catalytically grown on the surface of the plasma-activated carbon fibers to obtain modified carbon fibers, including: The carbon fiber was subjected to plasma activation treatment in a cavity filled with an argon-oxygen mixture at a power of 250~350W. A mixture of ethylene and hydrogen in a volume ratio of (3.5~4.5):1 is introduced into the cavity, and the mixture is reacted at 630℃~680℃ for 10~18 min to catalytically grow the carbon nanotube array on the surface of the carbon fiber, thereby obtaining the modified carbon fiber.

[0012] In some embodiments of this disclosure, the preparation method further includes, prior to melt impregnation extrusion of the modified carbon fiber and matrix resin: A functional slurry is coated on the surface of the modified carbon fiber to form a protective film on the surface of the modified carbon fiber; The modified carbon fibers forming the protective film are subjected to selective laser carbonization. The protective film has a thickness of 80~120μm; the functional slurry comprises the following components, the content of each component being expressed as a mass fraction as follows: 25-35 parts of polyetherimide 15-25 parts of sulfonated polyether ether ketone 40-60 parts of carbon nanotubes.

[0013] In some embodiments of this disclosure, the preparation method further includes, prior to melt impregnation extrusion of the modified carbon fiber and matrix resin: The matrix resin containing different concentrations of functional fillers is injected through a multi-stage dispensing system; the functional fillers include iron oxide-modified graphene. The graphene oxide modified with iron oxide is arranged in the matrix resin according to a preset rule by magnetic field treatment, and the graphene oxide modified with iron oxide is ionically bonded to the modified carbon fiber.

[0014] In some embodiments of this disclosure, the functional filler further includes a dynamic crosslinking agent containing pinacol groups; the matrix resin includes a polyethylene glycol amine-grafted bisphenol A type epoxy resin and a polyisocyanate-crosslinked polycarbonate; the preparation method further includes: The dynamic crosslinking agent containing pinacol groups connects the polyethylene glycol amine-grafted bisphenol A type epoxy resin and the polyisocyanate-crosslinked polycarbonate to form a three-dimensional network structure.

[0015] The beneficial effects of this disclosure include, but are not limited to: the carbon fiber composite material provided by this disclosure includes modified carbon fiber bundles and a matrix resin. The matrix resin coats the carbon fiber bundles and fills the gaps within the carbon fiber bundles. Carbon nanotube arrays are grown on the surface of the modified carbon fibers, which can enhance the physical bonding force between the modified carbon fiber bundles and the matrix resin, thereby significantly improving the mechanical properties of the carbon fiber composite material. Furthermore, the growth of carbon nanotube arrays on the surface of the modified carbon fibers can also form a highly conductive network near the modified carbon fibers, contributing to the improvement of the overall conductivity of the carbon fiber composite material.

[0016] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and are not intended to limit this disclosure. Attached Figure Description

[0017] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments of the present disclosure and, together with the description, serve to explain the principles of these embodiments. In these drawings, similar reference numerals are used to denote similar elements. The drawings described below are some embodiments of the present disclosure, but not all embodiments. Other drawings will be readily available to those skilled in the art based on these drawings without inventive effort.

[0018] Figure 1 This is a schematic flowchart of a method for preparing carbon fiber composite material according to an exemplary embodiment of the present disclosure; Figure 2 This is a schematic flowchart of a method for preparing carbon fiber composite material according to another exemplary embodiment of this disclosure; Figure 3 This is a schematic flowchart of a method for preparing carbon fiber composite material according to another exemplary embodiment of this disclosure; Figure 4 This is a schematic diagram of a method for preparing a carbon fiber composite material, which is another exemplary embodiment of this disclosure. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of this disclosure clearer, the technical solutions of this disclosure will be clearly and completely described below in conjunction with the embodiments of this disclosure. Obviously, the described embodiments are only some embodiments of this disclosure, and not all embodiments. Based on the embodiments in this disclosure, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this disclosure. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of this disclosure can be arbitrarily combined with each other.

[0020] Traditional carbon fiber composites generally suffer from poor interfacial bonding performance. The chemically inert and smooth surface of carbon fibers results in weak physical anchoring and chemical bonding between them and the resin matrix. This weak interfacial bonding severely restricts the overall performance of the material and affects the long-term durability and dimensional stability of the composite.

[0021] To address the aforementioned technical problems, this disclosure provides a carbon fiber composite material comprising modified carbon fiber bundles and a matrix resin. The matrix resin coats the carbon fiber bundles and fills the gaps within them. An array of carbon nanotubes is grown on the surface of the modified carbon fibers, which enhances the physical bonding between the modified carbon fiber bundles and the matrix resin, thereby significantly improving the mechanical properties of the carbon fiber composite material. Furthermore, the growth of the carbon nanotube array on the surface of the modified carbon fibers also forms a highly conductive network near the modified carbon fibers, contributing to an improvement in the overall conductivity of the carbon fiber composite material.

[0022] This disclosure provides a carbon fiber composite material comprising modified carbon fiber bundles and a matrix resin; the matrix resin coats the carbon fiber bundles and fills the gaps within the carbon fiber bundles; the modified carbon fiber bundles comprise modified carbon fibers, and the mass ratio of modified carbon fibers to matrix resin is 1.2~2.4; carbon nanotube arrays are grown on the surface of the modified carbon fibers, the height of the carbon nanotube arrays being 8~20 μm and the density being 60~120 nanotubes / μm. 2In the carbon fiber composite material provided in this embodiment, carbon nanotube arrays are grown on the surface of the modified carbon fibers. These carbon nanotubes are embedded in the surrounding matrix resin, mechanically locking the modified carbon fibers and the surrounding matrix resin together like micro-rivets. Furthermore, the growth of the carbon nanotube array on the surface of the modified carbon fibers increases the specific surface area of ​​the modified carbon fibers, significantly increasing the contact area between the modified carbon fibers and the matrix resin, improving the physical bonding force between the modified carbon fibers and the surrounding matrix resin, thereby greatly enhancing the mechanical properties of the carbon fiber composite material. In addition, the growth of the carbon nanotube array on the surface of the modified carbon fibers also forms a highly conductive network near the modified carbon fibers, contributing to the overall improvement of the conductivity of the carbon fiber composite material.

[0023] The angle at which carbon nanotube arrays grow on the surface of modified carbon fibers can be set as needed. For example, carbon nanotube arrays can grow perpendicularly on the surface of modified carbon fibers, or they can grow at any desired angle. For example, the carbon nanotube arrays can be at any angle to the tangent corresponding to the surface of modified carbon fibers, such as 10 degrees to 90 degrees.

[0024] The height of the carbon nanotube array is controlled between 8 and 20 μm to ensure that the array has sufficient length to provide effective interfacial reinforcement while balancing the flexibility of the carbon fiber composite. For example, the height of the carbon nanotube array can be 8 μm, 10 μm, 15 μm, 18 μm, or 20 μm, or any value within the exemplary range, such as any value between 10 and 18 μm. The density of the carbon nanotube array is controlled between 60 and 120 nanotubes / μm. 2 This ensures that the carbon nanotube array has a sufficient quantity to provide effective interfacial reinforcement, while also preventing brittleness or processing difficulties in carbon fiber composites due to excessive density. Furthermore, it guarantees that the gaps between the carbon nanotubes allow for matrix resin penetration, achieving full wetting of the matrix resin and thus avoiding interfacial defects. For example, the density of the carbon nanotube array can be 60 nanotubes / μm. 2 80 pieces / μm 2 100 pieces / μm 2 110 pieces / μm 2 Or 120 pieces / μm 2 The density of the carbon nanotube array can also be any value between the exemplary densities, for example, the density of the carbon nanotube array can be 70~110 nanotubes / μm. 2 Any value between.

[0025] The mass ratio of modified carbon fiber to matrix resin is 1.2 to 2.4, ensuring a high content of modified carbon fiber in the composite material. This provides excellent load-bearing capacity for the carbon fiber composite, while the matrix resin fully coats the modified carbon fiber and fills its internal gaps, preventing the formation of pores and defects. This allows the carbon fiber composite to maintain high strength and stiffness while being lightweight, making it suitable for applications with high weight and performance requirements, such as aerospace and automotive. For example, the modified carbon fiber can be plasma-activated carbon fiber. The mass ratio of modified carbon fiber to matrix resin can be, for example, 1.5, 1.8, 2.0, or 2.2. The mass ratio can also be any value between these exemplary mass ratios, such as any value between 1.5 and 2.2.

[0026] In the exemplary embodiments of this disclosure, the matrix resin comprises the following components, the content of each component being expressed in parts by mass as follows: 12.4~29.6 parts of bisphenol A type epoxy resin grafted with polyethylene glycol amine; 17.3 to 36.2 parts of polyisocyanate-crosslinked polycarbonate; 3.1 to 18.5 parts of γ-trifluoropropylmethylpolysiloxane.

[0027] In this embodiment, polyethylene glycol amine-grafted bisphenol A epoxy resin (epoxy equivalent 380-420 g / Eq) serves as the "main structural adhesive" and "reaction platform" of the matrix resin. It possesses high strength and rigidity, providing the primary load-bearing capacity for the carbon fiber composite. Furthermore, the polyethylene glycol amine-grafted bisphenol A epoxy resin effectively wets and bonds carbon nanotube-modified carbon fibers, which is crucial for forming a strong interface between the modified carbon fibers and the matrix resin. The use of polyethylene glycol amine-grafted bisphenol A epoxy resin enhances the flexibility of the epoxy resin by using polyethylene glycol segments, avoiding the brittleness of pure epoxy resin and improving its impact resistance. Moreover, the polyethylene glycol segments exhibit compatibility with polyisocyanate-crosslinked polycarbonate and γ-trifluoropropylmethylpolysiloxane, reducing phase separation among components in the matrix resin and thus enabling the formation of a uniform and stable three-phase matrix resin system. In this embodiment, the mass fraction of polyethylene glycolamine-grafted bisphenol A epoxy resin can be between 12.4 and 29.6 parts. Within this mass fraction range, the carbon fiber composite material can maintain sufficient strength and modulus while achieving significantly improved toughness and impact resistance. For example, the mass fraction of polyethylene glycolamine-grafted bisphenol A epoxy resin can be 12.4, 15.8, 22.7, or 29.6 parts. The mass fraction of polyethylene glycolamine-grafted bisphenol A epoxy resin can also be any value between the exemplary mass fractions, for example, the mass fraction of polyethylene glycolamine-grafted bisphenol A epoxy resin can be any value between 15.4 and 25.3 parts.

[0028] Polyisocyanate-crosslinked polycarbonate (glass transition temperature Tg ≥ 162℃) serves as the "heat-resistant skeleton" and "toughening phase" of the matrix resin. It exhibits high heat resistance and significantly improves the impact toughness and elongation at break of carbon fiber composites. Synergistically, it works with toughened polyethylene glycol amine-grafted bisphenol A epoxy resin, resulting in carbon fiber composites that are both strong and tough. Furthermore, the polyisocyanate crosslinking agent may react with the epoxy resin system, facilitating the formation of an interpenetrating polymer network, thereby further enhancing the phase-to-phase bonding in the matrix resin and improving the overall performance of the carbon fiber composite. In this embodiment, the mass fraction of polyisocyanate-crosslinked polycarbonate can be 17.3~36.2 parts. Within this range, the overall crosslinking density of the carbon fiber composite can be too high, affecting processing flowability, while providing sufficient toughening effect. For example, the mass fraction of polyisocyanate-crosslinked polycarbonate can be 17.3 parts, 25.8 parts, 30.7 parts, or 36.2 parts. The mass fraction of polyisocyanate-crosslinked polycarbonate can also be any value between the exemplary mass fractions, for example, the mass fraction of polyisocyanate-crosslinked polycarbonate can be any value between 20.4 and 28.3 parts.

[0029] γ-Trifluoropropylmethylpolysiloxane, acting as a "functional modifier" and "damper" for the matrix resin, exhibits excellent elasticity but relatively low strength and modulus. Adding a small amount to a rigid polyethylene glycol amine-grafted bisphenol A type epoxy resin / polyisocyanate crosslinked polycarbonate system can significantly improve the flexibility, fatigue performance, and damping loss factor of the carbon fiber composite without significantly reducing its overall strength, which is crucial for vibration reduction and noise reduction. Furthermore, γ-trifluoropropyl is a fluorine-containing group that significantly improves the hydrophobicity, weather resistance, chemical corrosion resistance, and oil resistance of the carbon fiber composite, enabling it to be used in harsh environments. Additionally, γ-trifluoropropylmethylpolysiloxane possesses good low-temperature performance, broadening the operating temperature range of the carbon fiber composite. In this embodiment, the mass fraction of γ-trifluoropropylmethylpolysiloxane can be 3.1 to 18.5 parts. Within this range, the flexibility of the carbon fiber composite can be improved without significantly reducing its mechanical strength and modulus. For example, the mass fraction of γ-trifluoropropylmethylpolysiloxane can be 3.1 parts, 5.4 parts, 12.7 parts, or 18.5 parts. The mass fraction of γ-trifluoropropylmethylpolysiloxane can also be any value between the exemplary mass fractions, for example, the mass fraction of γ-trifluoropropylmethylpolysiloxane can be any value between 5.4 and 16.3 parts.

[0030] In exemplary embodiments of this disclosure, the composite material further includes functional fillers, which comprise the following components, the contents of which are expressed in parts by mass as follows: 2.4–19.6 parts of iron(III) oxide-modified graphene; 0.5 to 8.9 parts of dynamic crosslinking agent containing pinacol groups.

[0031] Iron oxide-modified graphene is arranged in the matrix resin according to a preset rule, and ionic bonds are formed between the iron oxide-modified graphene and the modified carbon fibers. A dynamic crosslinking agent containing pinacol groups connects polyethylene glycol amine-grafted bisphenol A epoxy resin and polyisocyanate-crosslinked polycarbonate to form a three-dimensional network structure.

[0032] In this embodiment, sheet-like iron oxide-modified graphene (C / O ratio ≤ 1.85) is arranged in the matrix resin according to a predetermined rule, such as directional arrangement. For example, iron oxide is magnetic, and during the preparation of the carbon fiber composite material, an external magnetic field can be used to achieve the directional arrangement of the iron oxide-modified graphene in the matrix resin. The sheet-like iron oxide-modified graphene, directionally arranged in the matrix resin, acts like "bricks," while the matrix resin separating them acts like "mud." This structure effectively hinders crack propagation and improves toughness and stiffness. Furthermore, at the interface between the modified carbon fiber and the matrix resin, the carboxyl groups (-COOH) at the edges of the iron oxide-modified graphene form ionic bonds with the hydroxyl groups (-OH) and other functional groups on the surface of the modified carbon fiber after plasma activation. This is equivalent to building countless "nanobridges" between the modified carbon fiber and the matrix resin, greatly enhancing the interfacial bonding force between the modified carbon fiber and the matrix resin. In this embodiment, the mass fraction of iron oxide-modified graphene can be 2.4 to 19.6 parts. Within this mass fraction range, iron oxide-modified graphene can effectively enhance the toughness and stiffness of carbon fiber composites, strengthen the interfacial bonding between modified carbon fibers and matrix resins, and will not agglomerate due to excessive iron oxide-modified graphene, thus preventing a decrease in the mechanical properties of carbon fiber composites, such as toughness. For example, the mass fraction of iron oxide-modified graphene can be 2.4 parts, 5.7 parts, 13.8 parts, or 19.6 parts. The mass fraction of iron oxide-modified graphene can also be any value between the exemplary mass fractions, for example, the mass fraction of iron oxide-modified graphene can be any value between 4.4 and 16.8 parts.

[0033] Dynamic crosslinking agents containing pinacol groups can connect polyethylene glycol amine-grafted bisphenol A epoxy resin and polyisocyanate-crosslinked polycarbonate to form a three-dimensional network structure, improving the crosslinking density and toughness of carbon fiber composites, and also enabling the matrix resin to possess self-healing or remodeling capabilities. For example, when carbon fiber composites are damaged, the dynamic crosslinking agent containing pinacol groups can trigger the recombination of crosslinking points through heat or light, repairing microcracks and extending the lifespan of the carbon fiber composites. In this embodiment, the mass fraction of the dynamic crosslinking agent containing pinacol groups can be 0.5 to 8.9 parts. Within this mass fraction range, a dynamic crosslinking network can be formed within the carbon fiber composite, ensuring the self-healing function of the carbon fiber composite, while avoiding excessive use of the dynamic crosslinking agent containing pinacol groups, which would lead to excessive crosslinking density, increased brittleness, and reduced toughness. For example, the mass fraction of the dynamic crosslinking agent containing pinacol groups can be 0.5 parts, 2.4 parts, 5.3 parts, or 8.9 parts. The mass fraction of the dynamic crosslinking agent containing pinacol groups can also be any value between the exemplary mass fractions, for example, the mass fraction of the dynamic crosslinking agent containing pinacol groups can be any value between 1.2 and 6.5 parts.

[0034] In an exemplary embodiment of this disclosure, the mass ratio of the matrix resin to the iron oxide-modified graphene is (3.6~12.1):1.

[0035] In this embodiment, the mass ratio of the matrix resin to the iron oxide-modified graphene is controlled at (3.6~12.1):1. This ensures that the iron oxide-modified graphene has a sufficient concentration in the matrix resin to provide a significant reinforcing effect to the carbon fiber composite material, but without excessive concentration leading to agglomeration or reducing the flowability of the matrix resin, thus affecting the processability of the carbon fiber composite material. For example, the mass ratio of the matrix resin to the iron oxide-modified graphene can be 3.6:1, 5.2:1, 7.4:1, 9.5:1, or 12.1:1. The mass ratio of the matrix resin to the iron oxide-modified graphene can also be any value between the exemplary ratios, for example, the mass ratio of the matrix resin to the iron oxide-modified graphene can be any value between (4.6~11.5):1.

[0036] In the exemplary embodiments of this disclosure, the mass ratio of the sum of polyethylene glycolamine-grafted bisphenol A type epoxy resin and polyisocyanate-crosslinked polycarbonate to the dynamic crosslinking agent containing pinacol groups is (15.3~40.6):1.

[0037] Dynamic crosslinking agents containing pinacol groups can link polyethylene glycol amine-grafted bisphenol A type epoxy resin and polyisocyanate-crosslinked polycarbonate to form a three-dimensional network structure, improving the crosslinking density and toughness of carbon fiber composites, and also enabling the matrix resin to possess self-healing or remodeling capabilities. For example, when carbon fiber composites are damaged, the dynamic crosslinking agent containing pinacol groups can trigger the recombination of crosslinking points through heat or light, repairing microcracks and extending the lifespan of the carbon fiber composite. However, if the mass ratio of the sum of polyethylene glycol amine-grafted bisphenol A type epoxy resin and polyisocyanate-crosslinked polycarbonate to the dynamic crosslinking agent containing pinacol groups is too low, i.e., the content of the dynamic crosslinking agent containing pinacol groups is too high, the crosslinking points in the three-dimensional network structure will be too dense, making the carbon fiber composite brittle and reducing its impact toughness. When the mass ratio of the sum of polyethylene glycolamine-grafted bisphenol A type epoxy resin and polyisocyanate-crosslinked polycarbonate to the dynamic crosslinking agent containing pinacol groups is too high, i.e., the content of the dynamic crosslinking agent containing pinacol groups is too low, the resulting three-dimensional network structure will have insufficient dynamic crosslinking points, which will reduce the mechanical strength of the carbon fiber composite material and result in lower self-healing efficiency when the carbon fiber composite material is subjected to impact damage. Therefore, in this embodiment, the mass ratio of the sum of polyethylene glycolamine-grafted bisphenol A type epoxy resin and polyisocyanate-crosslinked polycarbonate to the dynamic crosslinking agent containing pinacol groups is controlled at (15.3~40.6):1. For example, the mass ratio of the sum of polyethylene glycolamine-grafted bisphenol A type epoxy resin and polyisocyanate-crosslinked polycarbonate to the dynamic crosslinking agent containing pinacol groups can be 15.3:1, 23.6:1, 34.1:1, 38.9:1, or 40.6:1. The mass ratio of the sum of polyethylene glycolamine-grafted bisphenol A type epoxy resin and polyisocyanate-crosslinked polycarbonate to the dynamic crosslinking agent containing pinacol groups can also be any value between exemplary ratios. For example, the mass ratio of the sum of polyethylene glycolamine-grafted bisphenol A type epoxy resin and polyisocyanate-crosslinked polycarbonate to the dynamic crosslinking agent containing pinacol groups can be any value between (19.4~35.6):1.

[0038] This disclosure provides a method for preparing carbon fiber composite materials, which is used to prepare carbon fiber composite materials as described above; Figure 1 As shown, the preparation method includes: S100. After plasma activation treatment of the carbon fibers in the carbon fiber bundle, carbon nanotube arrays are catalytically grown on the surface of the plasma-activated carbon fibers to obtain modified carbon fibers.

[0039] In step S100, after the carbon fibers in the carbon fiber bundle are subjected to plasma activation treatment, hydroxyl or carboxyl functional groups are introduced on the surface of the carbon fibers, which increases the surface energy of the carbon fibers, thereby enhancing the catalytic activity of carbon nanotube growth and the adhesion to the matrix resin.

[0040] Vertically oriented carbon nanotube arrays are catalytically grown on the surface of plasma-activated carbon fibers. These vertical carbon nanotubes embed themselves into the surrounding matrix resin, mechanically locking the modified carbon fibers and the surrounding matrix resin together like micro-rivets. Furthermore, the growth of carbon nanotube arrays on the modified carbon fiber surface increases the specific surface area of ​​the modified carbon fibers, significantly increasing the contact area between the modified carbon fibers and the matrix resin, and improving the physical bonding force between the modified carbon fibers and the surrounding matrix resin, thereby greatly enhancing the mechanical properties of the carbon fiber composite material. In addition, the growth of carbon nanotube arrays on the modified carbon fiber surface also forms a highly conductive network near the modified carbon fibers, contributing to the overall improvement of the conductivity of the carbon fiber composite material.

[0041] S200. Modified carbon fibers and matrix resin are melt-impregnated and extruded to obtain a carbon fiber composite material; wherein the matrix resin coats the carbon fiber bundles and fills the gaps within the carbon fiber bundles.

[0042] In step S100, the modified carbon fiber and matrix resin are melt-impregnated and extruded to ensure that the matrix resin fully coats the carbon fiber bundles and fills the gaps within the carbon fiber bundles, forming a dense carbon fiber composite material structure, reducing internal pores and defects in the material, and ensuring the overall mechanical properties of the material.

[0043] In exemplary embodiments of this disclosure, such as Figure 2 As shown, in step S100, after the carbon fibers in the carbon fiber bundle undergo plasma activation treatment, a carbon nanotube array is catalytically grown on the surface of the plasma-activated carbon fibers to obtain modified carbon fibers, including: S110. The carbon fiber is subjected to plasma activation treatment in a cavity filled with argon-oxygen mixture at a power of 250~350W.

[0044] The oxygen content in the argon-oxygen mixture can be 20% to 30%, for example, 20%, 25%, or 30%. The oxygen content can also be any value within the exemplary range, such as any value between 22% and 28%. The linear velocity of the carbon fiber plasma activation treatment can be 1.8 to 2.2 m / min, for example, 1.8 m / min, 2.0 m / min, or 2.2 m / min. The linear velocity of the carbon fiber plasma activation treatment can be any value within the exemplary range, such as any value between 1.9 and 2.1 m / min.

[0045] For example, the power of plasma activation treatment can be 250W, 300W or 350W, and the power of plasma activation treatment can also be any value between the exemplary powers, such as any value between 280 and 320W.

[0046] S120. A mixture of ethylene and hydrogen in a volume ratio of (3.5~4.5):1 is introduced into the cavity and reacted at 630℃~680℃ for 10~18 min to catalytically grow carbon nanotube arrays on the carbon fiber surface, thereby obtaining modified carbon fiber.

[0047] In this step, ethylene is used as the carbon source, and hydrogen is used as both a reducing agent and an etching agent to catalytically grow carbon nanotube arrays on the carbon fiber surface. The volume ratio of ethylene to hydrogen (3.5~4.5:1) ensures high-quality growth of the carbon nanotubes and avoids the formation of amorphous carbon. The volume ratio of ethylene to hydrogen can be, for example, 3.5:1, 4.0:1, or 4.5:1, or any value between these exemplary ratios, such as any value between 3.8~4.2:1. The reaction temperature can be, for example, 630℃, 650℃, or 680℃, or any value between these exemplary temperatures, such as any value between 640℃ and 670℃. The reaction time can be, for example, 10 min, 15 min, or 18 min, or any value between these exemplary times, such as any value between 12 and 16 min.

[0048] In exemplary embodiments of this disclosure, the modified carbon fibers and matrix resin are subjected to melt impregnation extrusion before, as... Figure 3 As shown, the preparation method of carbon fiber composite materials also includes: S201. A functional slurry is coated on the surface of the modified carbon fiber to form a protective film on the surface of the modified carbon fiber. The thickness of the protective film is 80~120μm.

[0049] A functional slurry is coated onto the surface of modified carbon fibers to form a protective film with a thickness of 80-120 μm. This provides protection for the modified carbon fibers during selective laser carbonization and imparts different functional modifications to the carbon fiber surface. The thickness of the protective film can be 80 μm, 100 μm, or 120 μm, or any value between these exemplary thicknesses, such as 90-110 μm.

[0050] The functional slurry comprises the following components, the content of which is expressed as a mass fraction as follows: 25-35 parts of polyetherimide; 15-25 parts of sulfonated polyether ether ketone; 40-60 parts of carbon nanotubes.

[0051] Polyetherimide, serving as both a "carbon source skeleton" and a "pore-forming agent" in functional slurries, is a precursor for high carbon yield. Polyetherimide is a high-performance engineering plastic containing numerous aromatic and imide rings in its molecular structure. This highly conjugated rigid structure prevents complete volatilization under inert atmospheres or laser pyrolysis, instead leading to cross-linking and cyclization reactions that leave behind a robust, conductive glassy carbon skeleton. This is the primary material basis for the formation of a conductive network after laser carbonization. Furthermore, even when polyetherimide is carbonized into a porous structure, the derived carbon skeleton retains a certain mechanical strength, enabling it to bond with the surrounding matrix resin and ensuring the structural integrity of the functional regions. Additionally, polyetherimide releases small molecule gases (such as CO2 and H2O) during pyrolysis. These gases escape from the viscous melt, contributing to the formation of a porous structure (porosity 62±3%), thereby increasing the specific surface area of ​​the modified carbon fibers. In this embodiment, the mass fraction of polyetherimide can be 25 to 35 parts. Within this mass fraction range, a continuous protective film can be formed on the surface of the modified carbon fiber, while avoiding excessive viscosity of the functional slurry due to excessive polyetherimide. For example, the mass fraction of polyetherimide can be 25, 28, 32, or 35 parts. The mass fraction of polyetherimide can also be any value between the exemplary mass fractions, for example, any value between 28 and 32 parts.

[0052] Sulfonated polyether ether ketone (PEE ketone) acts as a "catalyst" and "morphology modifier" in functional slurries, serving as a "catalyst" and "pore-forming agent" to lower the carbonization threshold. The introduction of highly polar sulfonic acid groups (-SO3H) into the PEE ketone molecular chain creates an acidic catalyst that significantly lowers the pyrolysis temperature of the surrounding polymer and promotes cross-linking reactions during carbonization. This means that more thorough and efficient carbonization can be achieved with lower laser energy, improving process efficiency and reducing thermal damage to the underlying modified carbon fibers. Furthermore, the sulfonic acid groups are highly unstable upon heating, decomposing and generating large amounts of gases (such as SO2 and H2O). This violent process is the primary driving force for the formation of high-porosity nanostructures, creating numerous micropores and mesopores, and significantly increasing the specific surface area of ​​the modified carbon fibers. In this embodiment, the mass fraction of sulfonated polyether ether ketone can be 15 to 25 parts. Within this mass fraction range, the pyrolysis temperature of the surrounding polymer can be significantly reduced, and the crosslinking reaction during its carbonization process can be promoted. Simultaneously, excessive sulfonated polyether ether ketone can prevent the hydrophilic sulfonated groups from absorbing moisture from the environment. For example, the mass fraction of sulfonated polyether ether ketone can be 15, 18, 20, or 25 parts. The mass fraction of sulfonated polyether ether ketone can also be any value between the exemplary mass fractions, for example, any value between 18 and 23 parts.

[0053] Carbon nanotubes act as both "laser carbonization inducers" and "macroscopic conductive network builders." When coated on the surface of modified carbon fibers, they absorb laser energy during laser carbonization, inducing localized carbonization and forming a conductive porous carbon structure. Furthermore, the carbon nanotubes in the functional slurry interlock, forming a continuous, macroscopic three-dimensional conductive network with the resulting carbides after laser carbonization. This three-dimensional conductive network is crucial for achieving a high specific capacitance (158 mF / cm²) in carbon fiber composites. 2 The above points form the basis for realizing electrode functions, enabling the application of carbon fiber composite materials in battery electrodes. Furthermore, the carbon nanotube arrays on the modified fiber surface act as "islands," while the conductive network formed after the functional slurry carbonizes is like an "ocean." This "ocean" of conductive network connects these "islands," forming a highly efficient conductive pathway throughout the entire carbon fiber composite material. In this embodiment, the mass fraction of carbon nanotubes can be 40-60 parts. Within this range, a continuous three-dimensional conductive network can be formed in the carbon fiber composite material, while avoiding excessive carbon nanotubes that could lead to agglomeration and negatively impact the mechanical properties of the carbon fiber composite material. For example, the mass fraction of carbon nanotubes can be 40, 45, 50, or 60 parts. The mass fraction of carbon nanotubes can also be any value within the exemplary range, such as any value between 45 and 55 parts.

[0054] S202. The modified carbon fiber that forms a protective film is subjected to selective laser carbonization.

[0055] Laser selective carbonization of modified carbon fibers that form a protective film can create patterned or gradient structures, which can introduce conductive pathways, enhance local strength, or achieve functional partitioning, thus enabling carbon fiber composites to be widely used in various fields.

[0056] In exemplary embodiments of this disclosure, the modified carbon fibers and matrix resin are subjected to melt impregnation extrusion before, as... Figure 4 As shown, the preparation method of carbon fiber composite materials also includes: S203, A matrix resin containing different concentrations of functional fillers is injected through a multi-stage dispensing system; the functional fillers include iron oxide-modified graphene.

[0057] By injecting matrix resins containing different concentrations of functional fillers through a multi-stage injection system, and injecting matrix resins with varying concentrations of iron oxide-modified graphene along the thickness direction of the component, a continuous and gradual change in the properties of carbon fiber composites can be achieved in the thickness direction. This optimizes overall performance and avoids problems caused by abrupt performance changes. Taking the carbon beam of a wind turbine blade as an example, its surface layer requires good electrical conductivity (for lightning protection and de-icing) or thermal conductivity, while the core layer mainly bears shear stress and does not require high electrical conductivity, but it needs excellent toughness. Therefore, when injecting the matrix resin, a matrix resin with a decreasing concentration of iron oxide-modified graphene can be injected from the surface layer to the core layer.

[0058] S204. Through magnetic field treatment, the iron oxide-modified graphene is arranged in the matrix resin according to a preset rule, and the iron oxide-modified graphene is ionically bonded to the modified carbon fiber.

[0059] After injecting matrix resin containing different concentrations of functional fillers through a multi-stage injection system, the carbon fiber composite is treated with a magnetic field to align the iron oxide-modified graphene in the matrix resin according to a predetermined rule, such as directional alignment, thereby enhancing the anisotropy of the carbon fiber composite. The directionally aligned iron oxide-modified graphene filler forms ionic bonds with the modified carbon fibers in the matrix resin, further strengthening the interfacial bonding between the matrix resin and the modified carbon fibers, reducing stress concentration, and improving the overall performance of the carbon fiber composite.

[0060] In exemplary embodiments of this disclosure, the functional filler further includes a dynamic crosslinking agent containing pinacol groups; the matrix resin includes polyethylene glycol amine-grafted bisphenol A type epoxy resin and polyisocyanate crosslinked polycarbonate; the method for preparing the carbon fiber composite material further includes: A dynamic crosslinking agent containing pinacol groups connects polyethylene glycol amine-grafted bisphenol A type epoxy resin and polyisocyanate-crosslinked polycarbonate to form a three-dimensional network structure.

[0061] Dynamic crosslinking agents containing pinacol groups can link polyethylene glycol amine-grafted bisphenol A type epoxy resin and polyisocyanate-crosslinked polycarbonate to form a three-dimensional network structure, improving the crosslinking density and toughness of carbon fiber composites, and also enabling the matrix resin to possess self-healing or remodeling capabilities. For example, when carbon fiber composites are damaged, dynamic crosslinking agents containing pinacol groups can trigger the recombination of crosslinking points through heat or light, repairing microcracks and extending the lifespan of carbon fiber composites.

[0062] The specific process of repair using a dynamic crosslinking agent containing pinacol groups can be as follows: When microcracks occur in carbon fiber composites, the carbon fiber composite component is heated at 180°C (e.g., in an oven or using a hot air gun for localized heating). This temperature is higher than the glass transition temperature (Tg) of the matrix resin, allowing the polymer chains to acquire sufficient mobility. The heating heat provides the necessary activation energy for the pinacol bond exchange reaction. At the crack interface, the dynamic pinacol bonds under stress break, releasing the stress. Simultaneously, these broken bonds become exceptionally active under thermal drive, continuously undergoing "breakage-reorganization" exchange reactions. This makes the polymer molecules on the crack surface no longer fixed, but in a dynamic, flowable state (similar to a very viscous liquid). Under the combined action of molecular thermal motion and interfacial tension, this "viscous" material on both sides of the crack gradually flows and diffuses into the crack. When the polymer molecular chains from both sides of the crack come into contact with each other, the pinacol functional groups on their surfaces reform new chemical bonds through dynamic exchange reactions. This means the cracks are no longer merely a physical adhesion, but rather the formation of entirely new, robust chemical bonds. After maintaining this state for 10 minutes, the heat source was removed, allowing the carbon fiber composite component to cool. The carbon fiber composite component re-cured, the dynamic exchange reaction rate decreased sharply, and the newly formed chemical bonds stabilized. The microcracks in the carbon fiber composite component disappeared, and the mechanical properties of the carbon fiber composite were restored.

[0063] In another embodiment, during the hot-pressing of the carbon fiber composite material layer by layer (at a temperature of 150-180°C), the heat activates the pinacol bond exchange reaction. The pinacol functional groups at the ends of the polymer molecular chains in adjacent layers of carbon fiber composite material (prepreg) "recognize" each other and undergo bond exchange reactions. Thus, a molecular chain originally belonging to layer A is directly connected to a molecular chain in layer B through a dynamic covalent bond. Numerous such reactions occur at the interlayer interfaces of the carbon fiber composite material, as if countless "molecular needles and threads" are "stitching" the two layers together. This "stitching" is a chemical bond, and its binding force is far stronger than traditional physical adsorption and mechanical interlocking, thereby significantly improving the interlayer shear strength and anti-delamination ability of the carbon fiber composite material.

[0064] In an exemplary embodiment of this disclosure, the method for preparing carbon fiber composite materials further includes: performing selective laser carbonization on the carbon fiber composite material and 3D printing it. On the same carbon fiber composite component, by precisely controlling the laser energy, regions with distinctly different properties can be created to meet the different requirements of different locations within the carbon fiber composite component. For example, when applying the carbon fiber composite component to a porous carbon electrode, a porous, high-specific-surface-area conductive carbon structure needs to be prepared in the high-energy storage region, while a dense, intact carbon fiber composite structure needs to be maintained in the high-strength region.

[0065] Laser selective carbonization functionalization and 3D printing can be performed simultaneously. Laser selective carbonization functionalization refers to directly creating regions with specific electrochemical or electrical functions inside or on the surface of a structure. This mainly includes: fabricating embedded electrodes (for structural supercapacitors to achieve energy storage), etching strain sensing circuits (for health monitoring to achieve self-sensing), and creating conductive pathways (for signal transmission or electromagnetic shielding). Essentially, it transforms the insulating matrix resin of carbon fiber composites into conductive porous carbon material through laser energy, thereby endowing it with the ability to transport electrons or adsorb ions.

[0066] For example, carbon fiber composite materials can be used in the aerospace field for satellite structural solar panels, wind turbine blade carbon beams in new energy equipment, and 3D printed bicycle frames in sports equipment, with a silicone rubber damping layer (thickness 0.3±0.05mm) integrated inside the frame tube wall, and a damping loss factor ≥0.12.

[0067] In one embodiment, a method for recycling carbon fiber composite materials according to an exemplary embodiment of this disclosure is provided: Waste carbon fiber composite material components are immersed in ethylene glycol solvent and treated at 180±2℃ for 4±0.5h. The immersion solution is centrifuged and sieved to recover carbon fibers, with a single filament tensile strength ≥4.2GPa. The supernatant from centrifugation is subjected to vacuum distillation to recover oligomers, with an epoxy equivalent change rate ≤5% after repolymerization. Iron oxide-modified graphene filler is recovered by magnetic separation in a 0.5T magnetic field, with a recovery rate ≥90%.

[0068] To more clearly explain the technical solutions provided by the exemplary embodiments of this disclosure, a specific example of the preparation method of the carbon fiber composite material provided by the exemplary embodiments of this disclosure is given.

[0069] Using 50K large-tow carbon fiber bundles, treated with ultrasonic-air blowing combined fiber spreading technology, the spacing between single filaments after spreading is ≤5μm.

[0070] The carbon fiber bundles were ultrasonically cleaned in acetone (frequency 40±5kHz, time 30±5min) and dried at 80±5℃ for 8h.

[0071] The cleaned carbon fiber bundles were placed in a chamber filled with an argon-oxygen mixture and subjected to plasma activation treatment at a power of 250-350W. The oxygen content in the argon-oxygen mixture was 20-30%, and the linear velocity of the plasma activation treatment was 1.8-2.2 m / min.

[0072] A mixture of ethylene and hydrogen in a volume ratio of (3.5~4.5):1 is introduced into the cavity and reacted at 630℃~680℃ for 10~18 min to catalytically grow carbon nanotube arrays on the carbon fiber surface, thereby obtaining modified carbon fiber.

[0073] A functional slurry is coated on the surface of modified carbon fiber to form a protective film with a thickness of 80~120μm on the surface of modified carbon fiber.

[0074] The modified carbon fibers forming the protective film were subjected to selective laser carbonization using a 1064nm fiber laser. Specifically, the high-energy storage region (electrode region) had the following parameters: power 8±0.5W, scanning rate 50±5mm / s, pulse frequency 80±5kHz, spot diameter 100μm, and porosity 62±3%; the high-strength region (border region) had the following parameters: power 2±0.2W, scanning rate 200±20mm / s, pulse frequency 30±3kHz, spot diameter 80μm, and density ≥95%.

[0075] The graphene oxide modified with iron oxide (Fe3O4) in the matrix resin is oriented and aligned within the resin by treating it with a magnetic field of 0.4–0.6 T for 8–15 min. The laser-modified carbon fibers and the matrix resin are then melt-extruded using a twin-screw extruder with the following process parameters: zone 1 220±5℃, zone 2 260±5℃, zone 3 280±5℃, and a winding speed of 3±0.3 m / min, to obtain the carbon fiber composite material.

[0076] Further, the prepared carbon fiber composite material was layered as follows: Layer 1: 0° (62% carbon fiber volume), Layer 2: +45° (functional area reserved cavity), Layer 3: -45° (embedded sensing circuit), and Layer 4: 90° (encapsulation layer). A 3D printing system with an integrated laser module was used for simultaneous forming and functionalization, with the following parameters: print head temperature 320±10℃; hot press roller parameters: temperature 150±5℃, pressure 0.8±0.1MPa; laser synchronization accuracy: laser focus lag behind the printing nozzle distance ≤1.5mm, resulting in a carbon fiber composite material part. The carbon fiber composite material part was then heat-treated in a 180℃ oven for 2 hours (heating rate 3℃ / min). It was then sealed by spraying γ-trifluoropropylsiloxane (film thickness 50μm).

[0077] Following the surface treatment methods described in the specific examples above, the content of each component in the carbon fiber composite material and the content of each component in the functional slurry used were adjusted. The carbon fiber composite materials were tested in Examples 1-13, and supercapacitors were manufactured. Tensile strength testing was performed according to ASTM D3039, areal capacitance testing according to IEC 62391, interlaminar shear strength testing according to ASTM D2344, and capacity retention testing after 1500 charge-discharge cycles according to GB / T 18287. See Table 1 for details. Table 1

[0078] Table 1 (continued)

[0079] As can be seen from Table 1, the carbon fiber composite material prepared by the exemplary embodiment of this disclosure has high mechanical properties and electrochemical functions, and is suitable for fields with high requirements for weight and performance, such as aerospace, automobiles, and wind turbine blades.

[0080] The above-described contents can be implemented individually or in various combinations, and all such variations are within the scope of this disclosure.

[0081] Finally, it should be noted that in this document, the terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0082] The above embodiments are only used to illustrate the technical solutions of this disclosure, and are not intended to limit it. Although this disclosure has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this disclosure.

Claims

1. A carbon fiber composite material, characterized by, The composite material comprises modified carbon fiber bundles and a matrix resin; the matrix resin coats the carbon fiber bundles and fills the gaps in the carbon fiber bundles; the modified carbon fiber bundles comprise modified carbon fibers, and the mass ratio of the modified carbon fibers to the matrix resin is 1.2-2.4; The modified carbon fiber has a carbon nanotube array grown on the surface, the height of the carbon nanotube array is 8-20 μm, and the density is 60-120 per μm 2 .

2. The carbon fiber composite material according to claim 1, characterized by, The matrix resin comprises the following components, and the content of each component is represented as follows in terms of mass fraction: polyethylene glycol amine grafted bisphenol A type epoxy resin 12.4-29.6 parts, polyisocyanate crosslinked polycarbonate 17.3-36.2 parts, γ-trifluoropropylmethyl polysiloxane 3.1-18.5 parts.

3. The carbon fiber composite material according to claim 2, characterized by, The composite material further comprises functional fillers, and the functional fillers comprise the following components, and the content of each component is represented as follows in terms of mass fraction: ferroferric oxide modified oxidized graphene 2.4-19.6 parts, dynamic crosslinking agent containing pinacol groups 0.5-8.9 parts; The ferroferric oxide modified oxidized graphene is arranged in the matrix resin according to a preset rule, and an ionic bond is formed between the ferroferric oxide modified oxidized graphene and the modified carbon fibers; The dynamic crosslinking agent containing pinacol groups connects the polyethylene glycol amine grafted bisphenol A type epoxy resin and the polyisocyanate crosslinked polycarbonate to form a three-dimensional network structure.

4. The carbon fiber composite material according to claim 3, characterized by, The mass ratio of the matrix resin to the ferroferric oxide modified oxidized graphene is (3.6-12.1):

1.

5. The carbon fiber composite material according to claim 3, characterized by, The mass ratio of the sum of the polyethylene glycol amine grafted bisphenol A type epoxy resin and the polyisocyanate crosslinked polycarbonate to the dynamic crosslinking agent containing pinacol groups is (15.3-40.6):

1.

6. A method for producing a carbon fiber composite material, characterized by, The preparation method is used for preparing the carbon fiber composite material according to any one of claims 1-5; and the preparation method comprises: After the carbon fibers in the carbon fiber bundles are subjected to plasma activation treatment, carbon nanotube arrays are catalytically grown on the surfaces of the carbon fibers after the plasma activation treatment, to obtain modified carbon fibers; The modified carbon fibers and the matrix resin are subjected to melt impregnation extrusion, to obtain the carbon fiber composite material; wherein the matrix resin coats the carbon fiber bundles and fills the gaps in the carbon fiber bundles.

7. The method of producing a carbon fiber composite material according to claim 6, characterized by, After the carbon fibers in the carbon fiber bundles are subjected to plasma activation treatment, carbon nanotube arrays are catalytically grown on the surfaces of the carbon fibers after the plasma activation treatment, to obtain modified carbon fibers, comprising: The carbon fibers are subjected to plasma activation treatment in a cavity filled with argon-oxygen mixed gas at a power of 250-350 W; A mixed gas of ethylene and hydrogen in a volume ratio of (3.5-4.5):1 is introduced into the cavity, and the reaction is carried out at 630-680 ℃ for 10-18 min, so as to catalytically grow the carbon nanotube arrays on the surfaces of the carbon fibers, to obtain the modified carbon fibers.

8. The method for producing a carbon fiber composite material according to claim 6, characterized by, Before the modified carbon fibers and the matrix resin are subjected to melt impregnation extrusion, the preparation method further comprises: functional slurry is coated on the surfaces of the modified carbon fibers, to form a protective film on the surfaces of the modified carbon fibers; the modified carbon fibers on which the protective film is formed are subjected to laser selective carbonization treatment; The thickness of the protective film is 80-120 μm; the functional slurry comprises the following components, and the content of each component is expressed by mass fraction as follows: Polyetherimide 25-35 parts, Sulfonated polyether ether ketone 15-25 parts, Carbon nanotubes 40-60 parts.

9. The method for preparing carbon fiber composite material according to claim 6, characterized in that, Before the modified carbon fiber and the matrix resin are extruded by melt impregnation, the preparation method further comprises: Injecting the matrix resin containing different functional filler concentrations through a multi-stage glue injection system; the functional filler comprises Fe3O4 modified oxidized graphene; Treating by a magnetic field to arrange the Fe3O4 modified oxidized graphene in the matrix resin according to a preset rule, and ionically bonding between the Fe3O4 modified oxidized graphene and the modified carbon fiber.

10. The method for preparing carbon fiber composite material according to claim 9, characterized in that, The functional filler further comprises a pinacol group-containing dynamic crosslinking agent; the matrix resin comprises polyethylene glycol amine grafted bisphenol A type epoxy resin and polyisocyanate crosslinked polycarbonate; and the preparation method further comprises: The pinacol group-containing dynamic crosslinking agent connects the polyethylene glycol amine grafted bisphenol A type epoxy resin and the polyisocyanate crosslinked polycarbonate to form a three-dimensional network structure.